Anthropometric Index for Predicting Abnormalities of Biomedical Examination in Indonesian Urban Areas - Septiyanti Septiyanti; Nur Pudji A. Taslim; Nurhaedar Jafar (International Journal Of Health Science, 2025)
Obesity is a problem in various parts of the world where its prevalence is increasing rapidly, both in developed and developing countries. It is estimated that there are 1.5 billion people in the world experiencing being overweight and obese. Obesity can occur because there is an imbalance between the energy from the incoming food greater than the energy used by the body. This study is aimed to determine the best anthropometric index to predict abnormalities in biomedical examination (inflammation and lipid profile) in adulthood in urban areas of Indonesia. The study was a cross-sectional study. The data were taken from Health Research (Riskesdas). The population in this study were those age 20-59 years both sexes. The analysis conducted in this study are univariate, bivariate, ROC analysis, and logistic regression analysis. The results indicate that in general obesity and central obesity increases with age, with the highest prevalence was in the 40-59 year age. In adults, cut-off point value based on BMI and waist circumference to predict cardiovascular disease risk in Indonesian society is lower than the WHO recommendation.